2002
DOI: 10.1046/j.0022-3042.2002.00773.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of GTP cyclohydrolase I gene expression in the human neuroblastoma SKN‐BE(2)M17: enhanced transcription in response to cAMP is conferred by the proximal promoter

Abstract: Fig. 4 Human GTPCH promoter activity is stimulated by 8Br-cAMP treatment. (a) GTPCH 5¢-flanking sequence showing restriction sites used for generating the luciferase reporter gene deletion constructs 1171GTPCHluc (DraI), 613GTPCHluc (HindIII), and 313GTPCHluc (AccIII). Also shown are putative Sp1, CRE, CCAAT-box and TATAbox like sequences located within the 313GTPCHluc construct. (b) SK-N-BE(2)M17 cells were transfected with GTPCHluc constructs and pCMV-b-gal DNA. Then, 5 mM 8Br-cAMP was added 18 h later and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(37 citation statements)
references
References 16 publications
2
34
1
Order By: Relevance
“…GTPCH1 activity is regulated by cAMP mediated pathway [26]. In the present study, Br-cAMP or Db-cAMP pretreatment to cells led to significant reversal of CRP-mediated inhibition of GTPCH1 activity (Fig 3c).…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations
“…GTPCH1 activity is regulated by cAMP mediated pathway [26]. In the present study, Br-cAMP or Db-cAMP pretreatment to cells led to significant reversal of CRP-mediated inhibition of GTPCH1 activity (Fig 3c).…”
Section: Resultsmentioning
confidence: 67%
“…In this context, cell permeable analogue of cAMP, 8 Br-cAMP, which activates protein kinase A has been shown not only to result in restoration of GTPCH1 activity [26], but also attenuation of eNOS dysfunction [31,32]. Importantly, Hashimoto et al [43] reported the activation of eNOS by cilostazol via a cAMP/PKA and PI3K/Akt dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Western blots were performed with a rabbit anti-human antibody (1:5000 dilution), 19 and a goat anti-rabbit immunoglobulin G secondary antibody (1:10 000 dilution, Oncogene Research Products, San Diego, Calif) as previously described. 18 -20 …”
Section: Western Blot Analysis For Gtpch I Proteinmentioning
confidence: 99%